2020
DOI: 10.1101/2020.02.13.948307
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increased metal tolerance and bioaccumulation of zinc and cadmium in Chlamydomonas reinhardtii expressing a AtHMA4 C-terminal domain protein

Abstract: The use of microalgal biomass for metal pollutant bioremediation might be improved by genetic engineering to modify the selectivity or capacity of metal biosorption. A plant cadmium (Cd) and zinc (Zn) transporter (AtHMA4) was used as a transgene to increase the ability of Chlamydomonas reinhardtii to tolerate 0.2 mM Cd and 0.3 mM Zn exposure. The transgenic cells showed increased accumulation and internalisation of both metals compared to wild type. AtHMA4 was expressed either as the full-length protein or jus… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Fortunately, cationic diffusion-stressed EST databases also expressed MTP1's upregulation, which confirmed its role in the detoxification of Cd [61]. MTP roles have also been shown to improve cadmium resistance and sequestration of C. reinahrdtii acidic vacuoles [63,64].…”
Section: Detoxification Of Heavy Metal Ions Using Transporter Genesmentioning
confidence: 77%
See 1 more Smart Citation
“…Fortunately, cationic diffusion-stressed EST databases also expressed MTP1's upregulation, which confirmed its role in the detoxification of Cd [61]. MTP roles have also been shown to improve cadmium resistance and sequestration of C. reinahrdtii acidic vacuoles [63,64].…”
Section: Detoxification Of Heavy Metal Ions Using Transporter Genesmentioning
confidence: 77%
“…T A B L E 1 The capability of several microalgae/cyanobacteria to remove heavy metals (reproduced from Kumar et al [38] In the same way, Ibuot et al [64] reported that expression of either the FL protein or the CT domain of a plant Cd and Zn transporter (AtHMA4) known to bind metals in C. reinhardtii with the increment of the bioaccumulation and internalization of both Cd(II) and Zn(II) ions. This phenomenon elucidated increased metal binding, rather than metal transit, was the primary cause of increased metal bioaccumulation.…”
Section: Transgenic Microalgaementioning
confidence: 99%
“…The generation and characterization of Cd-resistant and hypersensitive C. reinhardtii mutants have also been reported in studies of heavy metal tolerance (Samadani et al, 2018;Hanikenne, 2003;Hu et al, 2001). In particular, the overexpression of metal transporters in C. reinhardtii for bioremediation is an attractive approach; it may allow both increased metal accumulation into the cell and increased metal tolerance, such as by transfer of a toxic metal out of the cytosol and into an internal compartment (Ibuot et al, 2020;Ibuot et al, 2017). The genetic manipulation of C. reinhardtii has been shown to be successful in creating stable, inherited phenotypes (Pollock et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The genetic manipulation of C. reinhardtii has been shown to be successful in creating stable, inherited phenotypes (Pollock et al, 2017). Changes in the heavy metal biosorption capacity of C. reinhardtii have been reported in genetically modified strains (Ibuot et al, 2020;Cheng et al, 2019;Aksmann et al, 2014;Lin et al, 2013;Mayfield et al, 2007;Shimogawara et al, 1998).…”
Section: Introductionmentioning
confidence: 99%